T030 Guiding TMS by EEG/MEG to interact with oscillatory brain activity and associated functions. Issue 3 (March 2017) - Thut, G.
Abstract : This talk will consider to what extent specificity of TMS (and TACS) interventions can be enhanced by adding a temporal to the usual spatial dimension of targeting. The studies I will present take into account temporal patterns of ongoing electrical brain activity for tailoring TMS to interfere with brain functions. The emphasis will be on brain oscillations as potential targets, and entrainment by rhythmic stimulation as a potential approach, which corresponds to an interaction of brain stimulation with brain activity, as opposed to a simple perturbation. My talk will cover studies that use frequency-tuned rhythmic TMS (or tACS), combined with EEG/MEG recordings, to guide and document the effects of stimulation. It will highlight concepts as well as empirical support for entrainment of brain oscillations, associated performance changes in the context of parietal TMS to bias visual perception, and outline differences between online and offline effects.